2018
DOI: 10.1007/s10646-017-1880-6
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of freshwater snails (Radix balthica) exposed to the pharmaceutical sertraline under simulated predation risk

Abstract: Due to their potential for affecting the modulation of behaviour, effects of selective serotonin reuptake inhibitors (SSRIs) in the environment are particularly interesting regarding interspecies interactions and non-consumptive effects (NCEs) induced by predator cues in prey organisms. We evaluated the effects of sertraline (0.4, 40 ng/L, 40 µg/L) over 8 days on activity and habitat choice in the freshwater snail Radix balthica, on snails’ boldness in response to mechanical stimulation (simulating predator at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Sertraline is also an SSRI-type antidepressant, as citalopram above. Swedish researchers have studied the behavior of freshwater snails ( Radix balthica ) exposed to the pharmaceutical, observing a general lack of effects on the snail’s activity [ 57 ]. In contrast, the same researchers found that the fish species Eurasian perch ( Perca fluviatilis ) presented an exposure-dependent decrease in feeding habits with increasing sertraline concentrations at a µg/L level [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sertraline is also an SSRI-type antidepressant, as citalopram above. Swedish researchers have studied the behavior of freshwater snails ( Radix balthica ) exposed to the pharmaceutical, observing a general lack of effects on the snail’s activity [ 57 ]. In contrast, the same researchers found that the fish species Eurasian perch ( Perca fluviatilis ) presented an exposure-dependent decrease in feeding habits with increasing sertraline concentrations at a µg/L level [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, several behavioral endpoints have been monitored in an ample range of mollusk species. For instance, feeding and movement variables have been amply used to assess the sensitivity of gastropods to different toxicants and other sources of stress (Snider and Gilliam 2008 ; Hedgespeth et al 2018 ; Alonso and Valle-Torres 2018 ; Alonso 2021 ). From an ecological perspective, movement behaviors, such as time to reach the food, swimming capacity, and time to start normal activity, are directly related to animal fitness (Scott and Sloman 2004 ; Snider and Gilliam 2008 ; Alonso and Camargo 2009a ; Hellou 2011 ; Silva et al 2018 ; Alonso 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…behavioural modifications upon exposure to pharmaceuticals can be tracked in short exposure periods. For example, for the end-point such as re-emergence of antennae from the shell in freshwater snails (Radix balthica) upon exposure to sertraline, exposure duration 3 min was sufficient (Hedgespeth et al, 2018). However, the sub-lethal effects on ecosystem dynamics to evaluate species sensitivity, and effect of trophic interactions demand a longer exposure period (Jarvis et al, 2014).…”
Section: Challenges In Understanding the Sub-lethal Effects Of Pharma...mentioning
confidence: 99%